Repeat pneumococcal polysaccharide vaccination does not impair functional immune responses among Indigenous Australians. Issue 10 (6th October 2017) - Licciardi, Paul V; Hoe, Edwin; Toh, Zheng Quan; Balloch, Anne; Moberley, Sarah; Binks, Paula; Marimla, Rachel; Leach, Amanda; Skull, Sue; Mulholland, Kim; Andrews, Ross
Abstract : Indigenous Australians experience one of the highest rates of pneumococcal disease globally. In the Northern Territory of Australia, a unique government‐funded vaccination schedule for Indigenous Australian adults comprising multiple lifetime doses of the pneumococcal polysaccharide vaccine is currently implemented. Despite this programme, rates of pneumococcal disease do not appear to be declining, with concerns raised over the potential for immune hyporesponse associated with the use of this vaccine. We undertook a study to examine the immunogenicity and immune function of a single and repeat pneumococcal polysaccharide vaccination among Indigenous adults compared to non‐Indigenous adults. Our results found that immune function, as measured by opsonophagocytic and memory B‐cell responses, were similar between the Indigenous groups but lower for some serotypes in comparison with the non‐Indigenous group. This is the first study to document the immunogenicity following repeat 23‐valent pneumococcal polysaccharide vaccine administration among Indigenous Australian adults, and reinforces the continued need for optimal pneumococcal vaccination programmes among high‐risk populations.